Chinese patients with 3M syndrome: clinical manifestations and two novel pathogenic variants - Xu, Ningan; Liu, Kangxiang; Yang, Yongjia; Li, Xiaoming; Zhong, Yan (Frontiers in Genetics, 2023)
Background: 3M syndrome is a rare autosomal recessive disease, characterized by intrauterine and postnatal growth retardation, facial dysmorphism, large head circumference, and skeletal changes, has rarely been reported in the Chinese population. Methods: We describe the clinical manifestations and gene variants in four sporadic cases of 3M syndrome in Chinese individuals from different families. Results: All cases had significant growth retardation, relative macrocephaly, and typical facial features. Exome sequencing revealed that two patients with 3M syndrome had homozygous variants of the CUL7 gene: one novel pathogenic variant and one previously reported pathogenic variant; the other two patients were heterozygous for variants in OBSL1, one of which had not been reported previously. Clinical evaluation indicated that these Chinese patients with 3M syndrome shared similar recognizable features with those reported in patients of other ethnic backgrounds, but not all patients with 3M syndrome in this study had normal development milestones. Two patients underwent recombinant human growth hormone (rhGH) therapy and showed accelerated growth in the first two years; however, the growth rate slowed in the third year in one case. There were no obvious adverse reactions during rhGH treatment. Conclusions: We report one novel CUL7 and one novel OBSL1 mutation in patients with 3M syndrome. Children with short stature, specific facial features, and physical symptoms should be referred for genetic testing to obtain precise diagnosis and appropriate treatment. The effects of rhGH treatment on adult height requires long-term observation and study in a large sample.